Analyzing the Production System and Redesign it. Case Study in Company state of IBN-Majid. - Iman Asker Hawi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to improve the reality of the production system in the Ibn Majid Public Company by comparing its production method with the two methods (Just-in-time (JIT)) and (Materials Requirement Planning (MRP)) to find a method that can contribute to improving the production process in the company. In fact, the production system is one of the important systems at the industrial company, and any defect in the industrial organization and weak of its internal performance, or in the market is due to the defects and weaknesses in the production system.